The Factors Influencing Fluid Fertilizer Use Intensity among Onion Farmers in Brebes District, Central Java, Indonesia - Dwi Purnomo; Jamhari Jamhari; Irham Irham; Dwidjono Hadi Darwanto (International Journal of Agriculture System, 2016)
The behavior of the farmers to using the fertilizer could be influenced by some factors. The factors such as social environment, culture, agriculture differentiate the way of using intensity the fertilizer. That behavior can also be different to what fertilizer the farmers use. The study aims to identify and analyze the behavior of farmers in using intensity of the liquid fertilizer products. The research was conducted by using a survey approach through interviews and questions (questionnaire) to 100 respondents of onion farmers in Brebes District Central Java on April until May 2015. Factors affecting the using intensity were analyzed by using multiple linear regression analysis. As the result shows in this study show that the using intensity of the liquid fertilizer is influenced by the income, the experience in planting the onions, how large the land, the productivity of the onion, the cultivating season, the recommendations from other farmers, field trials, and recommendations from the fertilizer store. The implication of the study is the farmers behavior to using the fertilizer is not only influenced of rational factors but also influenced by psychosocial factors. Government efforts to educate farmers about the benefits and risks to using liquid fertilizer need involves both aspects.